69‐2: Development of Flexible Cover Window for Large Foldable Display with a Pen‐Touch Function. Issue 1 (28th June 2021) - Park, Youngjoo; Bang, Soyeon; Hwang, Byoung-Har; Jang, Sejin; Kwak, Taehyoung; Lee, JounHo; Kim, JeomJae; Yoon, SooYoung
Abstract : Colorless polyimide (CPI) film is one of promising candidates for a foldable display because of its excellent mechanical and optical properties. To achieve a good and high reliable foldability, engineers must take into account thickness for foldability and mechanical hardness for pen touch function. To compromise this trade‐off relationship, LG Display chose CPI as a base film of the cover window and double‐sided thin hard coating for a pen touch solution. This paper shows why LG Display choose the proposed configuration with detail data.